Positive results of serological tests for syphilis in pregnancy – diagnostic and therapeutic problems, report of two cases - Koper, Marta; Serwin, Agnieszka; Baran, Anna; Flisiak, Iwona (Dermatology Review/Przegląd Dermatologiczny, 2015)
Introduction. Undiagnosed and untreated syphilis in pregnancy may result in subsequent complications: early fetal loss, stillbirth, low birth weight of infants and newborns with congenital syphilis. Objective. To analyze diagnostic and therapeutic dilemmas of positive results of serological tests for syphilis (STS) in pregnancy. Case reports. We present two cases of pregnant women, hospitalized in our department due to positive results of serological tests for syphilis, performed during the antenatal visit. On the basis of patients' history, physical examination and STS results, early latent syphilis was diagnosed in the first patient; biological false positive reactions were considered in the second one. Both patients received procaine penicillin treatment. Conclusions. Screening for syphilis in pregnancy as a part of antenatal care and appropriate treatment with penicillin are the most effective interventions to prevent complications of syphilis in pregnancy. It is also important to adapt modern European Guidelines for management of syphilis to Polish conditions.